2017
DOI: 10.1016/j.ultsonch.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic investigations in sono-hybrid (ultrasound/Fe2+/UVC) techniques of persulfate activation for degradation of Azorubine

Abstract: Persulfate-based oxidation of recalcitrant pollutants has been investigated as an alternative to OH radical based advanced oxidation processes due to distinct merits such as greater stability and non-selective persistent reactivity of SO oxidant species. The present study has attempted to highlight mechanistic features of persulfate-based decolorization of textile dye (Azorubine) using sono-hybrid techniques of activation. Three activation techniques, viz. sonolysis, Fe ions and UVC light and combinations ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(22 citation statements)
references
References 54 publications
0
20
0
2
Order By: Relevance
“…Several advanced techniques in recent studies have been reported for wastewater treatment containing azo dyes [38][39][40]. Among various implemented methods for dye removal, the advanced oxidation process (AOP) is applied favorably to destroy resistant contaminants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several advanced techniques in recent studies have been reported for wastewater treatment containing azo dyes [38][39][40]. Among various implemented methods for dye removal, the advanced oxidation process (AOP) is applied favorably to destroy resistant contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…([AB92] 0 = 200 mg/L, temperature = 333 K, pH 5, [SPS] 0 = 0.5 mM)subsequently intervenes in a series of reactions (Eqs [31][32][33][35][36][37][38][39][40][41] which create either ClO 3 − or • OH[86][87][88][89]:…”
mentioning
confidence: 99%
“…Однако, окислительные процессы при активации персульфата одновременным воздействием УЗ и УФ (в системе {УФ/УЗ/S 2 O 8 2-}) являются относительно малоисследованными. Ранее установлено, что данная окислительная система является наиболее эффективной для деструкции трихлорэтилена [9] и азорубина [10], а также минерализации модельных стоков красильного производства [11]. Синергический эффект в системе {УФ/УЗ/HSO 5 -} также наблюдался при обесцвечивании водных растворов красителя Прямого оранжевого 26 [12].…”
Section: -unclassified
“…Textile effluents are among the major sources of environmental pollution worldwide. Textile dyes can be toxic to aquatic lives and many of them exhibit carcinogenic characteristics . Due to the presence of azo rings in their structures, dyes are chemically stable and recalcitrant to conventional biological treatment processes .…”
Section: Introductionmentioning
confidence: 99%